2007
DOI: 10.1093/jmt/44.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy on Health-Related Outcomes in Cardiac Rehabilitation: A Randomized Controlled Trial

Abstract: This study tested effectiveness of music therapy in improving health-related outcomes of cardiac rehabilitation patients. Using a randomized, controlled trial with follow-up, the study was conducted in an outpatient cardiac rehabilitation program in Ohio. Sixty-eight of 103 recruited patients, 30 to 80 years of age, completed the protocol through posttreatment. Physiological and psychological outcomes were measured. Cardiac rehabilitation patients were randomly assigned to cardiac rehabilitation only or to mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…These findings are consistent with a study by Chang and Chen (2005). Positive effects of music listening on anxiety were obtained in a study performed on health-related outcomes in cardiac rehabilitation (Mandel et al, 2007). Music therapy improved executive function and overall emotional adjustment, and lessened depression, sensation seeking and anxiety in brain-injured patients (Thaut et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with a study by Chang and Chen (2005). Positive effects of music listening on anxiety were obtained in a study performed on health-related outcomes in cardiac rehabilitation (Mandel et al, 2007). Music therapy improved executive function and overall emotional adjustment, and lessened depression, sensation seeking and anxiety in brain-injured patients (Thaut et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…The sample size was calculated using the sample size formula, with a 95% confidence interval and 80% power. Then, using simple random sampling, the participants were allocated to two groups, the trial (n = 30) and control (n = 30) groups (Mandel et al, 2007). Patients undergoing surgery on even and odd days were allocated to the trial and control groups, respectively.…”
Section: Data Collectionmentioning
confidence: 99%
“…A relatively strong depth of data on participant music selections was provided in six studies, which identified the music selection categories and the specific music sound tracks used (Andrada et al, 2004;Bruer, Spitznagel, & Cloninger, 2007;Chang et al, 2008;Mandel, Hanser, Secic, & Davis, 2007;McKinney, Antoni, Kumar, Tims, & McCabe, 1997;Shiraishi, 1997). Such provided helpful information to understand study results and to replicate intervention.…”
Section: Journal Of Nursing Researchmentioning
confidence: 99%
“…The most commonly used biological maker was cortisol level (Bittman et al, 2001;Leardi et al, 2007;McKinney et al, 1997;McRee et al, 2003;Suzuki et al, 2004). Six of 33 retrieved studies used physiological markers such as vital signs (Chlan, 1998;Guzzetta, 1989;Mandel et al, 2007;McRee et al, 2003;Sendelbach et al, 2006;White, 1992;Wong et al, 2001) and cerebral blood flow (Lazaroff & Shimshoni, 2000) as outcome measures. Among the 13 studies that used biological or physiological measurements, 12 also used some form of psychological method to obtain combined measurements.…”
Section: What Metrics Were Used For Outcome Measuresmentioning
confidence: 99%
“…7 An important nonpharmacological treatment already used for cardiovascular patients, and other patient populations, is music listening. Music has been used as a therapeutic tool for populations with cardiovascular diseases including coronary heart disease (CHD), 16 heart failure, 17 hypertension, 18 cardiac rehabilitation, 19 cardiac surgery, 20 and during cardiac diagnostic procedures. 21 Several investigators have found that listening to music influences QOL, 22 psychological distress, 23 anxiety, 24 depression, 25 mood, 26 blood pressure, 27 heart rate (HR), 28 and quality of sleep.…”
mentioning
confidence: 99%